2003
DOI: 10.1067/mcp.2003.3
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state pharmacokinetic interaction of modified‐dose indinavir and rifabutin

Abstract: Increasing indinavir's dose to 1000 mg every 8 hours when coadministered with rifabutin at a reduced dose of 150 mg daily compensates for rifabutin induction of indinavir metabolism. Rifabutin concentrations were still higher than with rifabutin alone despite a 50% reduction of rifabutin dose, which is the current recommendation when these 2 drugs are combined. The clinical significance of the increase in rifabutin and 25-desacetyl rifabutin concentrations is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…A rash occurs more frequently with a higher withdrawal rate in healthy subjects receiving FPV-RTV (7)(8)(9) than in HIV-infected patients receiving FPV-RTV (Lexiva [fosamprenavir calcium] product information, June 2006), which may in part reflect a different risk-benefit profile for patients and a true potential for less-frequent rashes in HIVinfected patients. Safety findings were also similar to those in other studies of protease inhibitors coadministered with RFB (2,3,5). Therefore, the coadministration of RFB and FPV-RTV does not appear to cause safety concerns in addition to those of either treatment alone.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A rash occurs more frequently with a higher withdrawal rate in healthy subjects receiving FPV-RTV (7)(8)(9) than in HIV-infected patients receiving FPV-RTV (Lexiva [fosamprenavir calcium] product information, June 2006), which may in part reflect a different risk-benefit profile for patients and a true potential for less-frequent rashes in HIVinfected patients. Safety findings were also similar to those in other studies of protease inhibitors coadministered with RFB (2,3,5). Therefore, the coadministration of RFB and FPV-RTV does not appear to cause safety concerns in addition to those of either treatment alone.…”
Section: Discussionsupporting
confidence: 76%
“…The combination of RFB (150 mg QOD) and FPV-RTV (700/100 mg BID) for 14 days had a side effect profile similar to previously described events with RFB or FPV-RTV alone (1,2). Neutropenia (absolute neutrophil count of Ͻ750/mm 3 ) has been found in 25% of subjects receiving RFB in efficacy studies (Mycobutin product information, February 2002) but has not been reported for healthy subjects receiving FPV with or without RTV (4,(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 89%
“…The addition of HIV protease inhibitors, such as ritonavir, atazanavir, indinavir, and saquinavir, all of which are known to be P-gp inhibitors, at 10 M (a concentration in the range or above clinically relevant plasma concentrations) (Hamzeh et al, 2003;Cook et al, 2004;McCance-Katz et al, 2007), did not significantly (p Ͼ 0.05) reduce the efflux. The strongest inhibition within this class of compounds was observed for ritonavir.…”
Section: Resultsmentioning
confidence: 98%
“…(Kashuba, 2005) Combined administration of antacids does not seem to significantly affect the amount absorbed of fosamprenavir, (Ford et al, 2005) or raltegravir; however it is recommended to separate the taking of the two drugs when they are used in pharmacological therapy. (Kiser et al, 2010) Aaron et al, 2004;Benator et al, 2007;Blumberg et al, 2003;DeJong et al 2004;Finch et al, 2002;Hamzeh et al, 2003;Kraft et al, 2004;La Porte et al, 2004;Polk et al, 2001;Ribera et al, 2007;Rolla et al, 2006;Spradling et al, 2002) Ritonavir (Aaron et al, 2004;Blumberg et al, 2003;DeJong et al 2004;Finch et al, 2002;Spradling et al, 2002) 1: very high risk 2: high risk Adjust rifabutin dose 150 mg/48 hours, with no change in ritonavir Indinavir (Hamzeh et al, 2003, Kraft et al, 2004 1: very high risk 2: high risk Adjust the dose of rifabutin 150 mg/24 hours and indinavir at 1,000 mg/8 hours Saquinavir (Aaron et al, 2004;Blumberg et al, 2003;DeJong et al 2004;Finch et al, 2002;Ribera et al, 2007;Rolla et al, 2006;Spradling et al, 2002) 1: very high risk 2: high risk Use usual dose of rifabutin (300 mg/day), with no change in saquinavir Nelfinavir (Aaron et al, 2004;Benator et al, 2007;Blumberg et al, 2003;DeJong et al 2004;…”
Section: Drug Interactions Related To Bioavailability 351 Drug Intementioning
confidence: 99%
“…This combination is considered absolutely contraindicated McCance-Katz et al, 2006;Matteelli et al, 2007a;Ramachandran et al, 2006;Ribera et al, 2001) Delavirdine (Borin et al, 1997;DeJong et al 2004;McCance-Katz et al, 2006;Spradling et al, 2002) Nevirapine (Benator et al, 2007;Blumberg et al, 2003;Borin et al, 1997;Burger et al, 2006;Hamzeh et al, 2003;Kraft et al, 2004;La Porte et al, 2004;Polk et al, 2001;Ramachandran et al, 2006;Ribera et al, 2001Ribera et al, , 2007Rolla et al, 2006) 2: high risk 3: medium risk…”
Section: : Very High Riskmentioning
confidence: 99%